THE POLICY OF TRAINING MANAGERIAL PERSONNEL IN THE PRESCHOOL EDUCATION SYSTEM OF THE REPUBLIC OF UZBEKISTAN (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article analyzes the issues of developing managerial potential of leadership personnel in the preschool education system of Uzbekistan and the introduction of innovative approaches in their activities. In particular, the content, assessment criteria, financial and organizational mechanisms of managerial training courses established in accordance with Resolution No. 531 dated August 27, 2024, are examined from a scientific-theoretical perspective. Furthermore, the role of learner-centered, modular, and digital technology-based teaching methods in shaping the professional competencies of leaders is substantiated. The article scientifically justifies the necessity of ensuring continuous professional development of leaders to organize effective management within the education system.